Pengaruh Leverage dan Firm Size terhadap Pengungkapan Corporate Social Responsibility (CSR) - Vicky Oktavian Kharisma; Erna Sulistyowati (Universitas Batanghari, 2022)
This study aims to examine the effect of Leverage, and Firm Size on Corporate Social Responsibility (CSR). The method used in this study is a quantitative method with secondary data in the form of an annual report or annual report obtained from the IDX website or each company. The sample selection technique used purposive sampling with a sample of 140 samples from 35 companies in the period 2017 to 2020. The data analysis technique in this study used multiple regression analysis with the help of SPSS software version 24. The results of this study indicate that partially Leverage variable has no effect. on Corporate Social Responsibility (CSR) and the Firm Size variable has an effect on Corporate Social Responsibility (CSR).